Feather picking / self-mutilating in psittacine birds. Recent data for the control - IORDANIDIS (Π. ΙΟΡΔΑΝΙΔΗΣ) P. (Journal of the Hellenic Veterinary Medical Society, 2017)
Feather picking /self-mutilating is the most frequent and serious problem of psittacine birds that the avian practitioners have to deal with in practice. The etiologic agents of this behavior may be infectious, parasitic, nutritional, but the most interesting among them are psychological (housing, environment, attention seeking etc). It is very difficult to establish accurate diagnosis, although some laboratory examinations may be helpful. Especially the behavioral history may be important for the identification of psychological causatives. Therapy of feather picking is not always possible. Pharmaceutical treatment, primarily with psychotropic drugs, improvement of the housing conditions and nutrition, closer relationship with the persons that the birds live with, may be useful to reduce or even to solve this problem. The prognosis is circumspect, because sometimes, in spite of the therapy, there is no improvement or it is temporary. Feather picking disorder is described in the present study. Recent data on the causative agents and the control of the disorder are also reported.